Disproportionality analysis of satralizumab in FDA adverse event reporting system and Japanese adverse drug event report: a pharmacovigilance study - Zhang, Linhai; Yan, Rong; Xu, Zucai (Frontiers in Immunology, 2026)
BackgroundTo date, no post-marketing safety studies of satralizumab have been conducted. This study aims to evaluate the post-marketing safety profile of satralizumab using data from the U.S. Food and Drug Administration (FDA) Adverse Event Reporting System (FAERS) and Japanese Adverse Drug Event Report (JADER) databases.MethodsWe extracted all adverse event (AE) reports related to satralizumab from the FAERS database covering the period from Q1–2023 to Q4 2024. Disproportionality analyses were conducted for AEs with at least four reports listing satralizumab as the primary suspect (PS), using Reporting Odds Ratio (ROR), Proportional Reporting Ratio (PRR), Bayesian Confidence Propagation Neural Network (BCPNN), and Multi-item Gamma Poisson Shrinker (MGPS), along with their corresponding 95% confidence intervals (CI). Non-parametric tests were applied to compare differences between serious and non-serious outcomes.ResultsSince its approval, a total of 2,527 AEs related to satralizumab have been reported in the FAERS database, involving 931 individual patients. Among them, 355 patients experienced serious outcomes, including 389 fatal cases. The most frequently reported AEs were infection-related, such as urinary tract infection (n = 72), infectious pneumonia (n = 44), COVID-19 (n = 43), sepsis (n = 23), and cellulitis (n = 17). In addition, several unexpected AEs were identified, including cerebral infarction and malignancies. Compared with patients experiencing non-serious outcomes, male patients were more likely to develop serious outcomes, which also tended to occur earlier in the treatment course. Furthermore, the standard usage (120 mg once every 2 weeks for three doses at Weeks 0, 2, and 4, followed by 120 mg once every 4 weeks) was associated with a relatively favorable safety profile.ConclusionThe adverse risks associated with satralizumab are notable. Our findings provide evidence to support risk assessment in clinical practice; however, high-quality clinical studies are still needed to validate these results and to further explore the long-term safety and efficacy of the drug.